Supplier Selection on Rendement Rate of Patchouli Leaf - Hanum, Bethriza; Izzati, Titia; Cakravastia, Andi (International Journal of Engineering and Technology, 2018)
The aim of research is to design the model of rendement rate by considering the criteria of patchouli leaf and designing a good supplier selection model to maximize the company profit by considering the acceptance of the patchouli oil rendement rate. The selection of suppliers discussed is to consider the quantity of goods offered by suppliers, demand, budget and acceptance limitation ofÂ  rendement rate. To overcome these limitations, it is necessary to develop a supplier selection model that takes into consideration the quantity limitation of goods offered by the supplier and the acceptance of the rendement rate by using Linear Programming (LP) method. The result of the research shows that the determination model of the rendement rate developed to determine the percentage of Rendement Rate (RR) of each raw material supplied by the supplier so that the company can know the quality of patchouli leaf based on the type of patchouli leaf. The analysis result of numerical sample calculation shows that the selected supplier is not a supplier with good patchouli leaf criteria, the analysis result of parameter changes in oil demand and budget indicate that when oil demand is increased over the benchmark data, the model output is insensitive, but when demand is lowered below the benchmark data, the model output looks sensitive.Â Â